2020
DOI: 10.17576/3l-2020-2601-12
|View full text |Cite
|
Sign up to set email alerts
|

Understanding English Speaking Practice in Public Schools in Kazakhstan: A Case Study in Almaty

Abstract: Teaching and learning of English as a spoken language in English as a Foreign Language (EFL) still remains a major concern in Asian context as evident from recent studies. The situation is similar in Central Asian classrooms where it received little attention. Specifically, this study investigates a classroom in a local public school in Kazakhstan through the lens of a teacher and the students during speaking activities. A case study qualitative approach was employed using interviews, classroom observations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The data were then analysed using thematic analysis (TA) developed by Braun and Clarke (2006, 2014 and Braun (2013, 2018) through both data-and theorydriven approaches (Braun & Clarke, 2006Maguire & Delahunt, 2017;Kiger & Varpio, 2020;Tuspekova et al, 2020). The data were classified into several themes according to the six stages in the implementation of TA -getting familiar with data, making initial codes, finding the themes, making reviews on the themes, giving names to the defined themes and making the report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were then analysed using thematic analysis (TA) developed by Braun and Clarke (2006, 2014 and Braun (2013, 2018) through both data-and theorydriven approaches (Braun & Clarke, 2006Maguire & Delahunt, 2017;Kiger & Varpio, 2020;Tuspekova et al, 2020). The data were classified into several themes according to the six stages in the implementation of TA -getting familiar with data, making initial codes, finding the themes, making reviews on the themes, giving names to the defined themes and making the report.…”
Section: Discussionmentioning
confidence: 99%
“…In this particular case, as an example, English teacher-1 (ET1) and English teacher-4 (ET4) provided students with open-ended questions (Teachers' Strategies-4, TS-4) to direct and encourage students to achieve critical thinking skills. This practice indicated that the openended questions were identified to help promote students' explicit expression of ideas (Tuspekova et al, 2020). However, before moving forward to critical questions, based on the results of observation (Obs.…”
Section: Teachers' Strategies To Promote Students' Critical Speaking ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The teaching method that the teacher uses is often assumed as the factor that causes the student's speaking problem. The current standard of English speaking proficiency among students does not reflect sufficient teaching and learning of speaking components (Tuspekova et al, 2020). There are lots of methods to encourage students' speaking ability communicatively.…”
Section: International Journal Of Language Teaching and Educationmentioning
confidence: 99%
“…It is believed that the use of English Language helps to benefit a person with the better economic and greater social interactions. This is proven as English was given the status of a "language of integration into the global economy" (Tuspekova, Mustaffa, & & Ismail, 2020). The fact that English is used as an alternative form of communication for countries where English is not the national language cannot be denied (proficiency) (Cawagdan & Rivera, 2018).…”
Section: Introductionmentioning
confidence: 99%